Teachers' Perceptions of Physics Scientific Argumentation Test Instruments Based on Modern Test Theory Using Question Modeling Through E-Learning Edpuzzle LMS - Sari, Alda Novita; Viyanti, Viyanti; Ertikanto, Chandra (Indonesian Journal of Science and Mathematics Education, 2023)
The study aims to understand teachers' perceptions of scientific argumentation test instruments in physics based on modern test theory using question modelling through Edpuzzle LMS e-learning. It employed a mixed method with a Sequential Explanatory Design. Data were collected through questionnaires and analyzed descriptively. Initially, it was found that 75% of teachers had not developed assessment instruments capable of optimally training students, resulting in 68% of students struggling to understand physics learning. Additionally, 54% of students reported having identified and solved complex physics problems using scientific argumentation, while 46% had not. Based on survey results, 95% of students and teachers agreed that assessment activities encourage scientific argumentation, indicated by identifying scientific issues and explaining scientific phenomena. Hence, there is a need for a physics scientific argumentation test model based on modern test theory. For future research, it is suggested to explore how integrating this test model in different educational settings impacts students' scientific argumentation skills and understanding of physics concepts.